Hydrogeological model and hydraulic behaviour of a large landslide in the Italian Western Alps - G. Pisani; M. Castelli; C. Scavia (Natural Hazards and Earth System Sciences, 2010)
A study of the large, deep-seated Rosone landslide (Italian Western Alps) is presented. A large amount of geological and geomechanical data has been collected in this area, due to the presence of various villages and man-made structures, and an automatic monitoring system was installed in December 2000. Since its installation, this system has been showing a continuous slow movement with periodical accelerations that can be correlated to heavy rainfall events. A hydrogeological model has been developed to study the influence of rainfall events on the pore pressure variations inside the rock slope. The structural characteristics, inclinometric and piezometric measurements, statigraphic and seismic profiles, geomorphologic information, water balance and chemical analyses of the main springs in the slope have been taken into account to consider this problem. A numerical hydraulic investigation, based on a continuum equivalent model of the landslide, has then been carried out using the FLAC3D computer code. Some preliminary results, which highlight the role of permeability and the porosity values of the rock mass on the pore pressure variations during heavy rainfall, are shown in the paper.